Microstructure and wear properties of Ni coated MoS2 self-lubricated coating. Issue 1 (11th June 2022) - He, Binfeng
Abstract: Ni based self-lubrication coatings were fabricated on the Ti6Al4V alloy by using laser cladding technique. The microstructures and properties of the coatings were studied in this work. The results illustrated that that the precipitates compounds are composed of dendrites, eutectic structure and petaloid-like compounds in the rapidly solidified molt pool. The EDS results shown that all of the phases are rich in titanium, nickel and carbon elements, combined with XRD pattern, it can be confirmed that these phases are mainly NiTi, NiTi2 and some of other compounds which appeared in N1 and N2 coating, but the compounds appeared in N3 coating is completely different. The average coefficient of the coatings is 0.7, 0.69 and 0.8, respectively. The friction coefficient curve of N3 coating rise up with the increase of sliding time which may be caused by the higher surface hardness, some of the hard particles may fall off during the sliding process, and abrasive wear mechanism aggravate at the interface. Some of the MoS2 decomposed because of the low melting point and oxidizing temperature, so the wear rates are 8.9 × 10 −7 mm 3 /(Nm) for N1 coating, 9.0 × 10 −7 mm 3 /(Nm) for N2 coating and 2.5 × 10 −7 mm 3 /(Nm) for N3 coating, respectively.